2020
DOI: 10.1111/jch.13923
|View full text |Cite
|
Sign up to set email alerts
|

A meta‐analytic evaluation of the diagnostic accuracy of the electrocardiographic Peguero‐Lo Presti criterion for left ventricular hypertrophy

Abstract: Although electrocardiography (ECG) is a cost‐effective and convenient tool for routine screening of left ventricular hypertrophy (LVH), its performance has been shown to be poor. The Peguero‐Lo Presti, a novel voltage criterion, was found to be potentially better than the most commonly used criteria. We conducted a systematic review and meta‐analysis of its diagnostic accuracy compared to Cornell and Sokolow‐Lyon voltage criteria. Bibliographic databases were searched to identify relevant articles. Pooled sens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 32 publications
0
3
2
Order By: Relevance
“…Indeed, in a recent systematic review and meta‐analysis, Peguero‐Lo Presti had a better pooled diagnostic performance based on ROC analysis, with an AUC of 0.83 compared to 0.72 and 0.62 for Cornell and Sokolow, respectively. 6 However, some other studies showed some discrepancies as our study does. In a Turkish population, Keskin et al found that although the Peguero‐Lo Presti criterion had higher sensitivity than the Cornell criterion (17.5% vs 9.7%), it had lower specificity (94.5% vs 98.2%) and slightly lower overall performance based on the AUC (0.64 vs 0.67).…”
Section: Discussioncontrasting
confidence: 88%
See 3 more Smart Citations
“…Indeed, in a recent systematic review and meta‐analysis, Peguero‐Lo Presti had a better pooled diagnostic performance based on ROC analysis, with an AUC of 0.83 compared to 0.72 and 0.62 for Cornell and Sokolow, respectively. 6 However, some other studies showed some discrepancies as our study does. In a Turkish population, Keskin et al found that although the Peguero‐Lo Presti criterion had higher sensitivity than the Cornell criterion (17.5% vs 9.7%), it had lower specificity (94.5% vs 98.2%) and slightly lower overall performance based on the AUC (0.64 vs 0.67).…”
Section: Discussioncontrasting
confidence: 88%
“…Several studies have shown a superiority of the Peguero‐Lo Presti criterion over the Cornell and Sokolow‐Lyon criteria. Indeed, in a recent systematic review and meta‐analysis, Peguero‐Lo Presti had a better pooled diagnostic performance based on ROC analysis, with an AUC of 0.83 compared to 0.72 and 0.62 for Cornell and Sokolow, respectively 6 . However, some other studies showed some discrepancies as our study does.…”
Section: Discussioncontrasting
confidence: 59%
See 2 more Smart Citations
“…A novel ECG criterion for LVH, proposed by Peguero et al [11], was recently shown to be more sensitive than traditional ECG-LVH criteria in patients with arterial hypertension. To date, the ability of the novel criterion to discriminate patients with and without anatomic LVH have been estimated in various clinical settings, including cardiac patients and the general population, demonstrating generally rather modest (and, at best, moderate) superiority over the classical ECG-LVH criteria in some [12][13][14][15][16], but not all [17][18][19][20][21][22][23]. However, to the best of our knowledge, only one study was focused on patients with aortic stenosis [24], the most prevalent valvular heart disease.…”
Section: Introductionmentioning
confidence: 99%